2013
DOI: 10.1111/ajt.12379
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Year Pathology Review of the Near Total Face Transplant

Abstract: In December of 2008, our institution performed a near total face transplant. The patient was monitored for signs of rejection assessed by paired skin and mucosa biopsies. The results of histological review of 120 biopsies collected during the first 4 years posttransplant are discussed. All biopsies were stained with hematoxylin and eosin, periodic acid-Schiff, immunohistochemical and TUNEL assays and graded using the Banff 2007 classification. Grade III rejection was diagnosed clinically at weeks 45 and 66, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…45 Site variation in determining in diagnosing and grading rejection must also be further explored, particularly in light of the robust study by Bergfeld et al, where examination of a large number of cutaneous and mucosal biopsies from a single face transplant patient indicated greater diagnostic sensitivity at the latter site. 29 Moreover, functional validation of the phenotypic findings presented herein will be required to more definitively understand the role of donor T cells in the rejection process. Finally, more comprehensive studies correlating detailed biomarker analysis of skin samples with systemic parameters of rejection are now indicated.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…45 Site variation in determining in diagnosing and grading rejection must also be further explored, particularly in light of the robust study by Bergfeld et al, where examination of a large number of cutaneous and mucosal biopsies from a single face transplant patient indicated greater diagnostic sensitivity at the latter site. 29 Moreover, functional validation of the phenotypic findings presented herein will be required to more definitively understand the role of donor T cells in the rejection process. Finally, more comprehensive studies correlating detailed biomarker analysis of skin samples with systemic parameters of rejection are now indicated.…”
Section: Discussionmentioning
confidence: 95%
“…21 However, clinical assessment, histopathological diagnosis, and immunological mechanisms of facial composite allograft rejection remain incompletely studied, albeit being critical to further refinement of this new treatment option. Although a number of important studies have begun to address the issue of biomarkers and related immunopathology in vascular composite allotransplantation [22][23][24][25][26][27][28][29] (particularly in hand transplantation), our study represents a detailed and sequential histopathologic and immunophenotypic assessment of full facial transplant rejection. Facial allografts represent a unique setting where rejection can be evaluated for cutaneous biomarker expression in multiple and sequential biopsies not required in routine skin allograft transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, both face and hand transplantations inflict far more surgical damage to both the recipient and donor tissue as compared to transplantation of internal organs resulting in larger surface area of disrupted and damaged tissue. This may partly explain the rate of acute graft rejections within the first year of such transplantations, which is 85% in hand transplantations and 84% in face transplantations, higher than any other field of transplantation [1215]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a review of rejection episodes occurring during the first 8 months also found clinical oral mucosal rejection was less common than skin (Kanitakis et al , ). Despite this, however, surveillance biopsies of otherwise normal appearing oral mucosa are more likely to demonstrate evidence of rejection histopathologically than skin (Kanitakis et al , ; Hui‐Chou et al , ; Bergfeld et al , ). Whether this is the result of the chronic low‐grade trauma of the oral mucosa or in fact a predictor of rejection (a possible subtype of acute rejection specific to the mucosa), or a more non‐specific process is unclear (Kanitakis et al , ; Hui‐Chou et al , ; Bergfeld et al , ).…”
Section: Discussionmentioning
confidence: 99%